PENGARUH METODE PEMBELAJARAN COMPLETE SENTENCE TERHADAP KETERAMPILAN MENULIS KALIMAT PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS III SD INPRES MALLENGKERI 1 KOTA MAKASSAR - Khairunnisa, Nur; Ratnawati, Ratnawati; Rahayu, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Complete Sentence learning method on the sentence-writing skills of third-grade students at SD Inpres Mallengkeri I, Makassar City. This study employed a quantitative approach using an experimental research design with a One-Group Pretest–Posttest Design. The sample consisted of 25 students. Data were collected through sentence-writing skill tests, observations, and documentation. The results showed that the students' mean pretest score of 63 increased to 79.4 on the posttest, indicating an improvement of 16.4 points. The results of the t-test revealed that the calculated t-value (13.21) was higher than the critical t-value (2.064), indicating that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the Complete Sentence learning method has a positive and statistically significant effect on the sentence-writing skills of third-grade students at SD Inpres Mallengkeri I, Makassar City.